Two-dimensional modeling of nitrate transport in canola field under Moistube irrigation using HYDRUS 2D/3D - Dirwai, Tinashe Lindel; Senzanje, A.; Mabhaudhi, T. (Frontiers Media, 2025)
Introduction: Understanding nitrate distribution and leaching under various irrigation strategies is critical for optimizing nitrogen use efficiency and minimizing environmental losses. While previous studies have explored wetting patterns under Moistube Irrigation (MTI) and discussed qualitative nitrate retention, few have quantitatively simulated nitrate transport through variably saturated zones with fine temporal-spatial resolution.